Non-Timber Forest Products (NTFP) in the Brazilian Amazon and Cerrado biomes: multi scale governance for Implementing enhanced socio-biodiversity chains - Carvalho Ribeiro, Sónia Maria; Jardim, Helder Lages; Ruchkys de Azevedo, Úrsula; Coelho, Vagner Braga Nunes; Bachi, Laura Salles; Soares-Filho, Britaldo Silveira (Sustainability in Debate, 2020)
Non-Timber Forest Products (NTFP), contribute to the livelihoods of over 6 million people in Amazon and over 4 million people in the Cerrado biomes. Here we explored data on the socio-ecology of extractivist landscapes at the biome scale in Amazonia and Cerrado in Brazil. We found that there are market chains for 45 and 58 NTFPs in Brazilian Amazon and Cerrado, respectively. Although there is a vast repertoire of empirical data for characterizing sociobiodiversity in Brazil this body of literature is mostly case-study driven, focusing on a very limited number of products and using different methodological approaches. Therefore, although there is a robust research legacy meaningful comparisons are very challenging. So far we have a fragmented view of vegetal extractivist dynamics at the biome scale. Our work contributes to upscale from the socioecology of individual NTFP to the biome scale encompassing a variety of products and its associated livelihoods.